2022
DOI: 10.1093/rheumatology/keab917
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of methotrexate-related adverse events in patients with early rheumatoid arthritis: results from a nationwide UK study

Abstract: Objectives To estimate prevalence rates and identify baseline predictors of adverse events (AEs) over the first year of treatment in patients with rheumatoid arthritis (RA) starting methotrexate (MTX). Methods Data came from the UK Rheumatoid Arthritis Medication Study (RAMS), a prospective cohort of patients with RA starting MTX. This analysis included patients aged ≥ 18 years with physician diagnosed RA and symptom duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
3
6
0
1
Order By: Relevance
“…and Greebe et al 23,25,27,37 . Among adverse events (occurring during therapy with MTX), gastrointestinal events were the most frequent (30.8–42%), followed by hepatotoxicity (15.1–20.2%), mucocutaneous (8.9–26.0%), neurological (5.5–28.6%), pulmonary (2.4–30.7%), and hematological side effects (5.2–5.6%) 38–40 . Similarly, the most frequent adverse events in our patients were hepatotoxicity (14.6%), nausea/emesis (14.1%), renal insufficiency (0.5%), medullary aplasia (1.5%), and pulmonary fibrosis (1.5%).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…and Greebe et al 23,25,27,37 . Among adverse events (occurring during therapy with MTX), gastrointestinal events were the most frequent (30.8–42%), followed by hepatotoxicity (15.1–20.2%), mucocutaneous (8.9–26.0%), neurological (5.5–28.6%), pulmonary (2.4–30.7%), and hematological side effects (5.2–5.6%) 38–40 . Similarly, the most frequent adverse events in our patients were hepatotoxicity (14.6%), nausea/emesis (14.1%), renal insufficiency (0.5%), medullary aplasia (1.5%), and pulmonary fibrosis (1.5%).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, several authors have reported longer drug survival in elderly psoriatic patients, and Sherbini et al found a decreased incidence of AEs in these patients. 26,27,38 Nevertheless, as early as 1989, some authors found that psoriasis in elderly patients could be controlled with a lower dose than the recommended and investigated some of the factors associated with the required dose. 41 Our results also showed that dosage >15 mg for a period of at least 3 months was a positive predictive factor for persistence in therapy and was negatively associated with suspension for both ineffectiveness and adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to MTX's folate antagonism, highly proliferative tissues such as the bone marrow and GI mucosa are particularly affected. The most common adverse effects include GI symptoms such as nausea, vomiting, diarrhea, mucositis, and mucosal ulcerations 26 . Additionally, patients commonly present with symptoms such as fatigue, dizziness, headache, cough, alopecia, and various types of cutaneous eruptions.…”
Section: Discussionmentioning
confidence: 99%
“…В недавно опубликованном британском когортном исследовании по крайней мере одно нежелательное явлений было зарегистрировано у 77,5% из 1069 больных ранним РА, которые впервые начали лечение метотрексатом. Чаще всего встречались желудочно-кишечные расстройства (42,0%), неврологические нарушения (28,6%), изменения со стороны кожи и слизистых оболочек (26,0%) и легких (20,9%), повышение активности печеночных аминотрансфераз (18,0%) и гематологические нарушения (5,6%) [25]. Основными побочными эффектами были тошнота (31,2%), утомляемость (29,4%) и головная боль (19,0%).…”
Section: клинический разборunclassified